Stability Analysis of Macroeconomic Effect on The Jakarta Composite Index (JCI) During 2006-2021 - Ningrum, Mersa Lestari; Matrodji H Mustafa (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This research aims to provide empirical evidence of macroeconomic effects on the Jakarta Composite Stock Price Index (JCI), precisely the exchange rate, GDP, gold prices, oil prices, and U.S. interest rates, as well as whether there are changes in the structure or stability of the regression during 2006-2021. The study employs quantitative research techniques such as panel data regression and dummy regression analysis with EViews 12. The results show that: (1) The exchange rate significantly negatively affects the JCI. (2) GDP significantly positively affect the JCI. (3) Gold prices significantly positively affect the JCI. (4) Oil prices significantly positively affect the JCI. (5) U.S. interest rates significantly positively affect the JCI. (6). The structure or stability regression of the macroeconomic effect on the JCI varies yearly. It means there is a change in the structure or stability of the regression during 2006-2021.